Osteoarthritis of the knee - a condemnation of a prosthesis for a young person? ATLAS Knee System as an effective method of relieving the medial compartment of the knee - Oliwer Sygacz; Jacek Walawski; Przemysław Żelazny; Joanna Filipczak; Aleksandra Swora; Joanna Borowik; Sebastian Bróż; Sara Dankiewicz; Wojciech Brodowski; Piotr Pawłowski; Katarzyna Basta-Arciszewska (Kazimierz Wielki University, 2022)
Introduction: Osteoarthritis of the knee is one of the more common causes of disability in the elderly. In the United States, one in four adults suffers from the condition, half of whom are under the age of 65. The most commonly affected joint is the knee. A significant proportion of people in the 35-65 age range have degeneration in one compartment of the knee joint. Among the younger population, when non-operative methods are already failing and it is too early for surgery, there is a place for the ATLAS Knee System. Aim of the study:  The purpose of our work is to present a new and innovative form of treatment for single-compartment osteoarthritis of the knee. Based on the available literature, to show the advantages, disadvantages and results of treatment with the ATLAS Knee System. Methods and materials: A literature review was conducted in the PubMed database, using the keywords: "Atlas Knee System"; "osteoarthritis"; "knee osteoarthritis". Results: The ATLAS system is built with an absorber that, as the knee is stretched, absorbs the forces acting on the medial compartment, while not putting stress on the rest of the knee joint. After patients use the implant, a significant reduction in pain and improvement in knee function is observed. Conclusion: Osteoarthritis is a significant health problem increasingly prevalent even among the younger population. The ATLAS system provides an alternative for younger people in whom conservative treatment has failed, while more invasive methods such as osteotomies and total or single-unit prosthetics are impossible or rejected by the patient. More studies are needed, on a larger number of people to accurately evaluate this system.